Microplastics in Mollusks: Research Progress, Current Contamination Status, Analysis Approaches, and Future Perspectives - Wang, Ruixuan; Mou, Hongli; Lin, Xiaozhi; Zhu, Hui; Li, Bing; Wang, Jiangyong; Junaid, Muhammad; Wang, Jun (Frontiers in Marine Science, 2021)
Plastic fragments < 5 mm, known as microplastics (MPs), are ubiquitously present in the marine environment. Research on MPs pollution has gradually shifted from field investigations to laboratory studies. With the rapid growth of plastic consumption and the prevalence of aquaculture products, studies on marine MPs have focused on key marine species, such as mollusks. This review will summarize the most recent research on MPs-mediated contamination in mollusks, focusing on three main topics: the main methods of MPs separation, extraction, and identification, the current state of shellfish microplastic pollution, and future research hotspots.